ADSORPTION OF RHODAMINE B USING FLOATING ?-CARRAGEENAN BEADS AS AN ADSORBENT - Tiara Putri, Bening
Rhodamine B is a synthetic dye that is commonly used in the textile, paper, and printing industries. In the textile industry, rhodamine B is used to dye cotton, wool, silk, leather, and bamboo. From that use, industrial waste will be produced which can pollute the waters. According to the World Health Organization (WHO), rhodamine B is quite dangerous because it could trigger cancer in humans. One method for rhodamine B removal in wastewater is using adsorption. In this research, floating ?-carrageenan beads adsorbent was made as an adsorbent from rhodamine B. Floating ?-carrageenan beads adsorbent was prepared by varying the type of carbonate salt and carbonate mass added. Floating ?-carrageenan beads were successfully prepared using a mixture of ?-carrageenan powder and CaCO3 with a mass ratio of 8:2. The adsorbent formed was characterized using the float test, swelling degree measurements, Fourier Transform Infrared (FTIR) analysis, and Scanning Electron Microscope (SEM). Based on the characterization results using FTIR, floating ?-carrageenan beads were successfully made showing a distinctive peak of ?-carrageenan in the fingerprint region. The floating ?-carrageenan beads had a floating time of 12 hours and a swelling degree of 763.35%. The adsorption performance of rhodamine B by floating ?-carrageenan beads was analyzed by measuring the remaining concentration of rhodamine B that was not absorbed from the solution using a UV-Vis spectrophotometer at a maximum wavelength of 557 nm using the calibration curve method. The optimum adsorption condition that was obtained was adsorption at pH 2 with an initial concentration of rhodamine of 100 mg g?1 and an adsorbent mass of 0.1 gram with a contact time of 120 minutes. The adsorption of rhodamine B using floating ?-carrageenan beads adsorbent followed the Sips adsorption isotherm model with a qm of 86,07±4,66 mg g–1and pseudo second order kinetics. Based on adsorption thermodynamics, it is found that adsorption is spontaneous and eksothermic as indicated by the ?G values of –26,83±0,82 (303 K), –27,72±0,85 (313 K), and –28,61±0,88 (323 K) kJ mol?1, and ?H of –4,17±0,84 kJ mo1?1 and ?S of 88,55±2,72 J mo1?1K?1 .